Effects and Mechanism of Zishen Jiangtang Pill on Diabetic Osteoporosis Rats Based on Proteomic Analysis. (25th September 2021) - Chu, Shufang; Liu, Deliang; Zhao, Hengxia; Shao, Mumin; Liu, Xuemei; Qu, Xin; Li, Zengying; Li, Jinhua; Li, Huilin
Abstract : Context . Zishen Jiangtang Pill (ZJP) is a Chinese herbal compound, which has a positive therapeutic effect on diabetic osteoporosis (DOP) by regulating glucose metabolism and bone metabolism. However, its regulatory role and mechanism are still unclear. Objective . To explore the effect and mechanism of ZJP on DOP rats by proteomic analysis. Materials and Methods . After the establishment of diabetes model by Streptozocin (STZ, 60 mg/kg), 40 Wistar rats were equally divided into normal group, model group (diabetic rats), high-dose group (3.0 g/kg/d ZJP), and low-dose group (1.5 g/kg/d ZJP) and received treatment for 3 months. Histological changes in bone and pancreas tissues were observed by hematoxylin and eosin staining, electron microscopy, and immunofluorescence. Proteomic and bioinformatic analyses were performed to identify the differentially expressed proteins. The fingerprint and active ingredients of ZJP were identified via high-performance liquid chromatography (HPLC). Results . Compared with the model group, ZJP could rescue the weight, fasting blood glucose, and fasting insulin of rats in both high-dose and low-dose group. ZJP could also improve the microstructures of pancreatic islet cells, bone mass, and trabecular and marrow cavities in DOP rats. Bioinformatic analysis suggested that ZJP might influence DOP via multiple pathways, mainly including ribosomes, vitamin digestion and absorption, and fat digestion and absorption. The primary active ingredients, including notoginsenoside R1, ginsenoside Rg1, ginsenoside Re, icariin, and ginsenoside Rb1, were detected. Conclusion . ZJP could significantly improve the histomorphology and ultrastructure of bone and islets tissues and might serve as an effective alternative medicine for the treatment of DOP.